PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN KONSUMEN GAME OF VALOR (Studi Kasus Pada Mahasiswa STIE Indonesia Pontianak) - Ana Yuliana; Ariputra Pratama (STIE 'INDONESIA' Pontianak, 2019)
This research was made by looking at data on the income of the mobile game industry during 2016 which reached US 40.6 billion (around Rp. 541 trillion), up 15% from the previous year's achievement of US 34.8 billion (around Rp. 480 trillion). The increase was partly due to the growth in revenue figures from the Android platform, which has increased by 32 percent over the previous year. Garena AOV (Arena of Valor) mobile game is one of Indonesian people's favorite mobile games that has attributes in the form of HD graphics (intel high definition), game system: true fair and interesting events. These three attributes are thought to affect the number of consumers who install and play the Garena AOV (Arena of Valor) mobile game. The number of samples in this study were 30 people, with criteria as users of the Arena of Valor game and the status of STIE Indonesia Pontianak students in the morning class of 2014-2017. Primary data from the questionnaire will be processed statistically using SPSS with the independent variable is hd (intel high definition), game system: true fair and event and the dependent variable is consumer decision. The results of this study are simultaneously independent variables significantly influence the dependent variable by 35.6%. Partially the independent variable has a significant effect on the dependent variable.